Application of the Problem Based Learning Model in Increasing Student Activity and Learning Outcomes in Beautiful Materials Mutual Respect - Muhammad Abdul Nafi' (FITK UIN Walisongo Semarang, 2025)
This research aims to increase the activeness and learning outcomes of grade V students in the material